The social mobilisation of conservative Malays against the injured Leviathan: a case study of Perkasa and ISMA from 2008 to 2017 - Tan, Chong Yew (2025)
This dissertation provides a critical account on how a reactionary Malay-Muslim social movement (SM) emerged and developed in Malaysia between 2008 and 2017. It examines the political opportunity structure (POS) in Malaysia and how two social movement organisations (SMOs) – Perkasa and ISMA – mobilised conservative Malays for collective actions. It is found that the POS is largely determined by state capacity to repress regime opponents. From a previously “robust Leviathan,” the Malaysian state has been reduced to an “injured Leviathan” following the 2008 general election. Using a component of Slater’s (2010) ordering power model, I explain how the decline in repression brought about a cognitive liberation (McAdam, 1999) among conservative Malays and created an opening for a reactionary movement in civil society. To understand the SM development, I have used frame analysis to identify ketuanan Melayu and Islamic populism as collective action frames (CAF) for Perkasa and ISMA respectively (Snow & Benford, 1988). To further elucidate their collective agency, I investigate their “frame alignment strategies” (Snow, et. al., 1986) to mobilise conservative Malays by examining various discourses on the New Economic Model (NEM), the Trans-Pacific Partnership Agreement (TPPA), the Allah row and the Coalition of Malaysian NGOs in the UPR Process (COMANGO). They are found to have employed frame amplification in discourses on globalisation and frame bridging for identity politics. Finally, this dissertation applies the concepts of injured Leviathan, frame amplification and frame bridging to make sense of contemporary Malaysian politics.